Screening for Glucose Perturbations and Risk Factor Management in Dysglycemic Patients With Coronary Artery Disease—A Persistent Challenge in Need of Substantial Improvement: A Report From ESC EORP EUROASPIRE V - Ferrannini, Giulia; De Bacquer, Dirk; De Backer, Guy; Kotseva, Kornelia; Mellbin, Linda; Wood, David; Rydén, Lars; Gale, Christopher P.; Beleslin, Branko; Budaj, Andrzej; Chioncel, Ovidiu; Dagres, Nikolaos; et al. (Diabetes care, 2020)
Dysglycemia, in this survey defined as impaired glucose tolerance (IGT) or type 2 diabetes, is common in patients with coronary artery disease (CAD) and associated with an unfavorable prognosis. This European survey investigated dysglycemia screening and risk factor management of patients with CAD in relation to standards of European guidelines for cardiovascular subjects. The European Society of Cardiology's European Observational Research Programme (ESC EORP) European Action on Secondary and Primary Prevention by Intervention to Reduce Events (EUROASPIRE) V (2016-2017) included 8,261 CAD patients, aged 18-80 years, from 27 countries. If the glycemic state was unknown, patients underwent an oral glucose tolerance test (OGTT) and measurement of glycated hemoglobin A . Lifestyle, risk factors, and pharmacological management were investigated. A total of 2,452 patients (29.7%) had known diabetes. OGTT was performed in 4,440 patients with unknown glycemic state, of whom 41.1% were dysglycemic. Without the OGTT, 30% of patients with type 2 diabetes and 70% of those with IGT would not have been detected. The presence of dysglycemia almost doubled from that self-reported to the true proportion after screening. Only approximately one-third of all coronary patients had completely normal glucose metabolism. Of patients with known diabetes, 31% had been advised to attend a diabetes clinic, and only 24% attended. Only 58% of dysglycemic patients were prescribed all cardioprotective drugs, and use of sodium-glucose cotransporter 2 inhibitors (3%) or glucagon-like peptide 1 receptor agonists (1%) was small. Urgent action is required for both screening and management of patients with CAD and dysglycemia, in the expectation of a substantial reduction in risk of further cardiovascular events and in complications of diabetes, as well as longer life expectancy.